2019
DOI: 10.3390/met9050613
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation Investigation on the Size-Dependent Creep Behavior in a Zr-Cu-Ag-Al Bulk Metallic Glass

Abstract: Nanoindentation technology has been widely adopted to study creep behavior in small regions. However, nanoindentation creep behavior of metallic glass is still not well understood. In the present work, we investigated nanoindentation size effects on creep deformation in a Zr-based bulk metallic glass at room temperature. The total creep strain and strain rate of steady-state creep were gradually decreased with increasing holding depth under a Berkovich indenter, indicating a length-scale-dependent creep resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
4
24
1
Order By: Relevance
“…the loading stage before the actual creep. This stage is considered to be of high importance and the material response during this step will affect dramatically the next step of creep response [5][6][7][8][9][10]. Close examination of the loading stage in Fig.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…the loading stage before the actual creep. This stage is considered to be of high importance and the material response during this step will affect dramatically the next step of creep response [5][6][7][8][9][10]. Close examination of the loading stage in Fig.…”
Section: Results and Analysismentioning
confidence: 99%
“…As Li et al [4] and other workers ever after showed, grain size, applied load/indentation depth, loading rates and creep holding time are the most crucial parameters that affect the creep response of a material. These parameters were, in a way, formulated for the creep response assessment, in factors such as the Indentation Size Effect (ISE) and the Loading Rate Sensitivity (LRS) and used in various different cases as in the works of Zhang et al [5], Ding et al [6], Lin et al [7], Choi et al [2] and Ma et al [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…An example is illustrated in the work by Glee et al [7] where, in order to avoid any influence from the substrate, miniaturized cylindrical tensile specimens of bond coatings were produced by a special grinding process, exposed to different environments and then creep tested. On the other hand, Ding et al [8] focused on the nanoindentation technology, also suitable for small material regions characterization. The technique has been used in [8], using both a Berkovich and a spherical indenter, on a Zr-based bulk metallic glass to investigate its creep behaviour at room temperature and to evaluate at the same time the effects of testing parameters.…”
Section: Innovative Testing Techniques Of Creep Deformationmentioning
confidence: 99%
“…On the other hand, Ding et al [8] focused on the nanoindentation technology, also suitable for small material regions characterization. The technique has been used in [8], using both a Berkovich and a spherical indenter, on a Zr-based bulk metallic glass to investigate its creep behaviour at room temperature and to evaluate at the same time the effects of testing parameters.…”
Section: Innovative Testing Techniques Of Creep Deformationmentioning
confidence: 99%
“…Constant load method is the most widely used method due to the simple measurement and rapid data collection. With the constant load method, much research has been done to study the creep deformation of thin films [28][29][30][31][32][33][34][35][36][37][38]. Specifically, Huang et al [38] demonstrated the feasibility of a high temperature nanoindentation creep study on ion irradiated oxide dispersion strengthened alloy.…”
Section: Introductionmentioning
confidence: 99%